2020
DOI: 10.1109/access.2020.3008155
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Function-Based Adaptive Neuro Network Sliding Mode Vibration Control for Flexible Double-Clamped Beams With Input Saturation

Abstract: In this paper, a novel adaptive neuro network nonsingular fast terminal sliding mode control based on barrier Lyapunov functions is proposed for flexible double-clamped beam systems with input saturation and distributed disturbance. First, the Galerkin projection method is employed to reduce the partial differential dynamic equations of the beam into ordinary differential equations. Second, a novel barrier Lyapunov function is employed to design a nonsingular fast terminal sliding mode controller that ensures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…One of the methods for the rejection of the matched disturbances is the usage of the adaptive-based barrier function. This method guarantees fast convergence of the trajectories of the system when it is combined with other control methods [ 26 , 27 , 28 ]. Moreover, this method is robust against variation of the perturbations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods for the rejection of the matched disturbances is the usage of the adaptive-based barrier function. This method guarantees fast convergence of the trajectories of the system when it is combined with other control methods [ 26 , 27 , 28 ]. Moreover, this method is robust against variation of the perturbations [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Reference 12, a quasi‐adaptive SMC algorithm with barrier function‐based gain was proposed for the motion control problem of a hydraulic servo‐mechanism to hold design error within a predefined domain. In Reference 13, an adaptive neural network nonsingular fast terminal SMC was designed based on BLF for a flexible double‐clamped beam in form of a SISO nonlinear system with state constraints. In Reference 14, a BLF‐based nonsingular fast terminal SMC with fixed‐time nonrecursive disturbance observer was presented for a blended‐wing‐body aircraft in the presence of output constraints.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the aforementioned control laws for spacecraft formation flying system are mainly based on the sliding mode control [34]- [36]. Since sliding mode control is an efficient control approach to enhance the system robustness against complex effects, such as model parameter perturbations [37] and external disturbances [38].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by solving the above challenging problems, as a novel form of singular free terminal sliding mode control, in this paper we aim to investigate a novel fast integral terminal sliding mode control law for spacecraft formation flying system subject to external disturbances and parameter uncertainties. The contributions can be summarized as follows, 1) Compared with [36], the novel modified fast integral terminal sliding mode control law is proposed, with which the formation stability in finite time is achieved, and kinematic couplings, external disturbances, parametric uncertainties are considered simultaneously.…”
Section: Introductionmentioning
confidence: 99%